(untitled) (Environment & Health, 2020)
A state of hyperhomocysteinemia was revealed in the large number of examined children living under conditions of constant radiation exposure. At the same time, taking into account the connection of homocysteine with the processes of osteogenesis, it is important to show the connection of calcium and phosphorus with hormones that regulate mineral metabolism, including the state of the folate cycle genome. Objective: We identified the correlations between blood levels of calcium, phosphorus, and hormones regulating mineral metabolism, taking into account the state of genome of folate metabolism in children living in a district suffered from the accident at the Chornobyl nuclear power plant. Methods: We used immunochemical and mathematical-and-statistical methods. Results: When examining children living in the area suffered from the accident at the Chornobyl nuclear power plant, the largest proportion of cases of hyperhomocysteinemia was found in the groups with T/T MTHFR: 677 and G/G MTR: 2756 genotypes. In children living in the area suffered from the accident at the ChNPP, P, in comparison with Ca, has closer links with hormones that regulate mineral metabolism. In children living under conditions of constant radiation exposure, the bearing of T/T MTHFR: 677genotype, accompanying by the severe hyperhomocysteinemia, contributes to the formation of the inverse correlation of the medium force between Ca and TSH. At the same time, there are no correlations between Ca and PTH, Ca and P in all genetic groups of the folate cycle. There was no connection between P and PTH in the groups of 100% bearing of risk alleles of MTHFR: C677T and MTR: A2756G polymorphisms. There were no connections of P with hormones that regulate mineral metabolism in the groups with homozygous bearing of noted risk alleles (genotypes T/T MTHFR: 677 and G/G MTR: 2756). A decrease in the activity of methylenetetrahydrofolate reductase and B12-dependent methionine synthase enzymes, in connection with the bearing of risk alleles of MTHFR: C677T and MTR: A2756G genetic polymorphisms, leads to impaired physiological regulation of phosphoric metabolism. Assessment of calcium-phosphorus metabolism in children from the areas suffered from the accident at the Chornobyl NPP should be carried out taking into account the level of homocysteine in blood and the genotype of folate cycle. The obtained results can be used in the development of the program on the prevention of mineral metabolism disorders in children living in the areas suffered from the accident at the ChNPP.